2012
DOI: 10.1673/031.012.8801
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofPseudomonas aeruginosaElastase B on Level and Activity of Immune Proteins/Peptides ofGalleria mellonellaHemolymph

Abstract: Susceptibility of proteins and peptides present in immune hemolymph of Galleria mellonella Fabricius (Lepidoptera: Pyralidae) larvae to proteolytic degradation by purified elastase B of Pseudomonas aeruginosa was studied. Results showed that apoLp-III protein was gradually digested by elastase B in vitro. Additionally, polipeptides with molecular mass 6.5 and 4 kDa were degraded after treatment with the studied enzyme. The lack of these peptides and the decrease in anti-Escherichia coli activity could indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…While the crucial role of QS in the P. aeruginosa infection to insects is often documented (Chugani et al ., ; D'Argenio et al ., ), the responsible virulence effectors regulated by QS were not fully clarified. Some studies have suggested that the factors related with twitching motility that is under the control of QS are important in the Pseudomonas virulence in Drosophila model system (Glessner et al ., ; D'Argenio et al ., ), and elastase B (LasB), another QS‐regulated exoprotease of P. aeruginosa can stimulate the humoral immune response at early stage of infection, and then degrade some immune components at later stage in G. mellonella model system (Andrejko and Mizerska‐Dudka, 2011; 2012). However, it was reported that the twitching motility is not directly related to the fly killing (D'Argenio et al ., ), and our result showed that LasB is not crucially involved in the virulence to T. molitor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the crucial role of QS in the P. aeruginosa infection to insects is often documented (Chugani et al ., ; D'Argenio et al ., ), the responsible virulence effectors regulated by QS were not fully clarified. Some studies have suggested that the factors related with twitching motility that is under the control of QS are important in the Pseudomonas virulence in Drosophila model system (Glessner et al ., ; D'Argenio et al ., ), and elastase B (LasB), another QS‐regulated exoprotease of P. aeruginosa can stimulate the humoral immune response at early stage of infection, and then degrade some immune components at later stage in G. mellonella model system (Andrejko and Mizerska‐Dudka, 2011; 2012). However, it was reported that the twitching motility is not directly related to the fly killing (D'Argenio et al ., ), and our result showed that LasB is not crucially involved in the virulence to T. molitor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Elastase A and B have been shown to drive host invasion by reducing the action of exotoxins, which delay the latter process. Elastase B acts against the host immune system by degrading complement proteins, immunoglobulins A and G, and inhibiting phagocytosis (Andrejko and Dudka, 2012). There have been reports suggesting a possible role of elastase B in mediating the degradation of surfactant proteins A and D in the lungs of cystic fibrosis patients (Mariencheck et al ., 2003).…”
Section: Virulence Factors Of P Aeruginosa: An Arsenal Of Sophisticat...mentioning
confidence: 99%
“…Larvae were surfaced sterilised with 70% ethanol (Thermo Fisher Scientific), sacrificed using a sterile disposable surgical scalpel (Swann-Morton) and hemolymph collected into a pre-chilled eppendorf tube containing 10-20 crystals of N-phenylthiourea (Alfa Aesar) to prevent further melanisation. 40 Optical density (OD) was measured at 450nm using an ELx800 plate reader (Biotek).…”
Section: Galleria Mellonella Melanisation Assaymentioning
confidence: 99%